Identifying risks the safety of elderly patients with dementia: integrative review (Research, Society and Development, 2020)
This is an integrative review study with the objective of identifying the risks to the safety of elderly patients with dementia. The research took place in the Medline, Bdenf and Lilacs databases, covering complete articles in electronic format, in english, Portuguese and Spanish in the period from 2015 to 2020. After the analysis according to the study criteria, 29 articles were selected that constituted the sample of this review. The risks found were analyzed from the perspective of patient safety and described in eight categories involving the international patient safety goals of the World Health Organization, the risks of functional losses related to cognitive deterioration, the risks of functional loss associated with psychological changes and behavioral of dementia and security risks associated with hospitalization. The identification of security risks for the elderly with dementia is fundamental for the management of safe care. The progression of cognitive deficit predisposes the elderly individual with dementia to risks that can be prevented or mitigated through the perspective of patient-centered care.